Factors related to export intensity of Filipino agripreneurs - De Castro, Melodee Marciana (2018)
This paper aims to determine the factors related to the intensity of Filipino agripreneurs. Secondary data from the Global Entrepreneurship Monitor (GEM) Philippine economy database were utilized.
Keywords: Agricultural economics; International economic relations; Agripreneurship; Association of Southeast Asian Nations